(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Premessa - 2. La preparazione del biennio sinodale - 3. Il dibattito sulle proposte di snellimento dei processi matrimoniali nell’Assemblea Straordinaria del 2014 - 4. La preparazione dell’Assemblea Ordinaria e l’accoglienza della riforma in Sinodo - 5. Conclusioni. Reflections on the Synodal origin of the processus brevior coram Episcopo. ABSTRACT: The aim of this paper is to demonstrate how the main aspect of the motu proprio Mitis Iudex Dominus Iesus signed by Pope Francis - the role of judge accorded to the Bishop especially in the new briefer process - cannot be linked to the suggestions of the two assemblies of the Synod of Bishops on the Family summoned in 2014 and 2015, as the Pontiff himself and many Authors have instead affirmed. Attention is mainly given to the documents of the first gathering: the preliminary questionary, the Instrumentum laboris, the mid-Synod relations and the Relatio finalis offered as a draft for the 2015 Assembly. The analysis of these documents prove that many of those involved in the synodal process showed great concern on the perspective of a Bishop acting himself as a judge, openly suggesting to avoid this solution. In the conclusion, a reflection is made on how the process that conducted to this reform often lacked those principles of synodality and collegiality frequently described as Francis’ key principles in the Church’s guidance.